The Possible Mechanisms of Firms’ Work After Covid-19 Pandemic - Zoubi, Orwa Al (Research Papers, 2023)
This study aims to research the possible changes in the mechanisms of firms’ work after Covid-19 pandemic. It implements a qualitative method by taking a purposive sample of 32 managers and deputies who were interviewed online at 8 companies in Austria. The results revealed that three companies achieved great success due to the nature of their work. Two companies achieved success due to new organizational and marketing mechanisms that were strongly taken to adapt to the new crisis. As for the remaining companies, the administrative slack and excessive bureaucracy prevented them from overcoming the repercussions of the crisis.